Determining the frequency of Streptococcus pneumoniae carriers and its microbial resistance in children - Lei, Langhuan; Wang, Xingyong (Cellular and Molecular Biology, 2022)
Streptococcus pneumoniae is a common cause of bacterial infections of the respiratory system, middle ear infection, bacteremia, meningitis, and pneumonia, especially in children. Due to the lack of information about the frequency and resistance of Streptococcus pneumoniae to antibiotics, the present study was performed to determine the frequency of carriers of Streptococcus pneumoniae and its microbial resistance in children. For this purpose, the current descriptive cross-sectional study was conducted from November to March 2020 on 554 children aged 2-12 years in kindergartens and schools. This study collected samples with a sterile swab from the nasopharyngeal region, transported them to the laboratory by a transport medium, and then cultured them on an agar culture medium. After isolation, confirmatory tests and antibiotic susceptibility were performed. The results were analyzed using SPSS16 software and interpreted according to Mann Whitney U and Chi-Square Tests. Streptococcus pneumoniae was found in 15% of samples, and the antibiotic resistance of the isolates to the antibiotics azithromycin, amoxicillin, rifampicin, amoxicillin-clavulanic acid, trimethoprim/Sulfamethoxazole, and ceftriaxone were 63.9%, 56.6%, 41%, 37.3%, 37.3%, and 3.6%, respectively. Also, 31.1% of the isolates were not resistant to any antibiotics. According to the results, excessive use of antibiotics has led to high resistance to azithromycin, amoxicillin, amoxicillin/clavulanic acid, and trimethoprim/Sulfamethoxazole, which indicates an increased risk of refractory infectious diseases. For this reason, it is necessary to adequately educate physicians and the general public about the overuse of antibiotics.